Factors Influencing Honey Choice in Slovakia and Hungary: A Comparative Study - Peter Šedík; Marián Čvirik; Cristina Bianca Pocol; Titanilla Oravecz (Amfiteatru Economic, 2025)
The study investigates extrinsic and intrinsic factors that influence honey purchasing decisions and their impact on honey consumption in Slovakia and Hungary. The comparative study is based on an online survey carried out during 2022. Both research samples are representative in terms of gender and age. They include honey consumers aged 18 years and older. An exploratory factor analysis (EFA) was used to investigate the relationships between 20 selected factors. The findings showed the existence of several latent factors, with slight differences between the two countries. In the Slovak honey market, four latent factors were identified: quality, price, marketing and visual factors, while in the Hungarian honey market six latent factors were identified: quality, marketing, geographic, product design and visual factors. In addition, cohort analysis showed statistically significant differences between the generations (Gen Z, Gen Y, Gen X, and Babyboomers) in both countries. The findings provide valuable insights into consumer preferences when selecting honey, which can help beekeepers develop customer-focused marketing strategies.